Speech by Prof. Daniel Mugendi, Principal Embu Uiniversity college to first year students ﻿2015 - Mugendi, Daniel N. (My University, 2015)
Speech by Prof. Daniel Mugendi, Principal Embu University College to First Year Students on Thursday, 3rd September 2015 at 10.00 A.M.
Keywords: First Year Students